Phylogenetic and structural analysis of annexins in pea (Pisum sativum L.) and their role in legume-rhizobial symbiosis development - O. A. Pavlova; I. V. Leppyanen; D. V. Kustova; A. D. Bovin; E. A. Dolgikh (Вавиловский журнал генетики и селекции)
Annexins as Ca2+/phospholipid-binding proteins are involved in the control of many biological processes essential for plant growth and development. In a previous study, we had shown, using a proteomic approach, that the synthesis of two annexins is induced in pea roots in response to rhizobial inoculation. In this study, phylogenetic analysis identified these annexins as PsAnn4 and PsAnn8 based on their homology with annexins from other legumes. The modeling approach allowed us to estimate the structural features of these annexins that might influence their functional activity. To verify the functions of these annexins, we performed comparative proteomic analysis, experiments with calcium influx inhibitors, and localization of labeled proteins. Essential down-regulation of PsAnn4 synthesis in a non-nodulating pea mutant P56 (sym10) suggests an involvement of this annexin in the rhizobial symbiosis. Quantitative RT-PCR analysis showed that PsAnn4 was upregulated at the early stages of symbiosis development, starting from 1–3 days after inoculation to up to 5 days after inoculation, while experiments with the Ca2+ channel blocker LaCl3 revealed its negative influence on this expression. To follow the PsAnn4 protein localization in plant cells, it was fused to the fluorophores such as red fluorescent protein (RFP) and yellow fluorescent protein (YFP) and expressed under the transcriptional regulation of the 35S promoter in Nicotiana benthamiana leaves by infiltration with Agrobacterium tumefaciens. The localization of PsAnn4 in the cell wall or plasma membrane of plant cells may indicate its participation in membrane modification or ion transport. Our results suggest that PsAnn4 may play an important role during the early stages of pea-rhizobial symbiosis development.